Multi-omics analysis reveals the panoramic picture of TOP2A in pan-cancer - Jin Zhang; Tianxiao Yang; Kenie Wang; Jie Pan; Junjun Qiu; Shengnai Zheng; Xuesong Li; Guanghao Li (Scientific Reports)
Abstract Topoisomerases are critical nuclear enzymes that resolve DNA topological challenges during genetic processes. However, there is currently a lack of comprehensive multi-omics analysis of TOP2A from a pan-cancer perspective, despite its significance. A multiomics analysis was conducted to investigate TOP2A across various cancer types. This study involved the integration of over 10,000 multidimensional genomic datasets from 33 distinct cancer types, obtained from The Cancer Genome Atlas (TCGA). The analysis focused on evaluating the overall activity levels of TOP2A in pan-cancers, which encompassed differential expression, clinical significance, immune cell infiltration, and the regulation of pathways related to cancer. Aberrant epigenetic modifications and genomic alterations have been identified as being associated with the dysregulation of TOP2A expression levels. These molecular changes have substantial impacts on cancer progression, intratumoral heterogeneity, immunological status, and the regulation of pathways related to cancer biomarkers. Consequently, patient prognosis varies significantly based on the presence and specific nature of these alterations. The potential of TOP2A to serve as a novel biomarker for prognosis may offer valuable insights into the diagnosis and treatment of cancer.